Is diversification of farm households still an option for integrated rural development? Evidence from Slovenia and Saarland, Germany - Nienaber, Birte; Slavič, Irma Potočnik (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2013)
Multifunctionality of rural areas in Europe has become an important aspect of rural development in the last years. An important instrument to ameliorate the multifunctionality is diversification of farm income. As various forms of farm income diversification have been developed throughout Europe, the paper will survey the effectiveness of undertaken measures. First the issue of farm diversification will be argued theoretically. Then case studies from Saarland, Germany, and from Slovenia will analyse the importance of diversification for rural areas. A comparison of the two regions will reveal the chances and risks of diversification in a comparable new and old EU member state.
Keywords: farm; on- and off-farm income diversification; rural development; Saarland; Slovenia